(untitled) (Innovative professional education, 2025)
The article demonstrates that using case-based learning enhances practical skills, critical thinking, and the ability to make informed decisions in energy conservation. It also identifies key principles for designing energy-efficiency case studies. Finally, the article offers recommendations for their integration into professional training of future qualified workers